The impact of banking uncertainty on firm investment: A look into intangible assets - Japan Huynh; Thi Minh Hue Phan (PLoS ONE, 2026)
This study examines the impact of banking uncertainty on intangible investments, in the context that there has been a growing body of literature addressing the ramifications of aggregate uncertainty on overall investment or physical investment. Based on data from 619 non-financial listed companies and 40 commercial banks in Vietnam between 2007 and 2022, we perform empirical regression analysis using the dynamic generalized method of moments (GMM) estimations since firms’ investment behavior is significantly persistent. We make our investigations more relevant and comprehensive by considering banking uncertainty in Vietnam’s bank-based market and delving into the underlying mechanisms through which banking uncertainty impacts corporate investments. Our findings reveal that firms tend to curtail their intangible asset investments in response to higher banking sector uncertainty, albeit the magnitude of the impact is economically weak. Differently, banking uncertainty substantially constrains investments in tangible fixed assets. We further provide evidence on financial conditions (captured by the cost of debt, financing constraints, and firms’ bank debt) as a driving force underlying the relationship between banking uncertainty and tangible assets, but not intangible investments. Our results remain robust after considering alternative variables, accounting for potential structural disruptions arising from crises, and addressing potential endogeneity concerns.